FACTORS THAT INFLUENCE THE PREGNANCY RATE IN BIOTECHNOLOGIES APPLIED ON RURAL PROPERTIES IN THE WEST GOIANO LÁCTEO APL - Clara Oliveira Costa, Maria; Althair Ribeiro Cordeiro, Fábio; Aurélio Souza Ramos, Marco; Teixeira da Silva, Jhonata; Pedro Pinheiro dos Santos, João; José Gonçalves dos Santos, Klayto (Journal of Interdisciplinary Debates, 2023)
The present study sought to investigate the effect of the degree of the corpus luteum, how the inovulation was performed (left or right) and season of the year related to forage availability, on the pregnancy rate of crossbred heifers submitted to TETF (embryo transfer in fixed time). This is a retrospective study that analyzed data recorded by BIOTEC (Center for Biotechnology in Animal Reproduction) belonging to the State University of Goiás, West Campus, located in São Luís de Montes Belos. The records had records of the diagnosis of pregnancy, inovulated horn and degree of corpus luteum of 206 females who received cryopreserved embryos from IVF. The transfers were carried out between February and August 2021. The data were represented in tables and later analyzed and discussed, in order to assess the effect of the aforementioned factors on the pregnancy rate of recipients in this analyzed group. Testing the hypotheses of several authors, it was verified: The degree of CL did not influence the pregnancy rate at 30 days of the recipients; The pregnancy rate at 30 days in recipients was higher in inovulations performed in the left horn, adjacent to the left ovary with the presence of CL; The pregnancy rate was higher in autumn compared to winter and summer.